Clinical course of infants with congenital heart disease who developed thyroid dysfunction within 100 days - Hye Jin Lee; Hyeoh Won Yu; Gi Beom Kim; Choong Ho Shin; Sei Won Yang; Young Ah Lee (Korean Society of Pediatric Endocrinology, 2017)
Purpose We investigated the clinical course of infants with congenital heart disease (CHD) who experienced thyroid dysfunction within 100 days of birth. Methods We performed retrospective medical reviews of 54 CHD patients (24 male patients) who underwent a thyroid function test (TFT) between January 2007 and July 2016. Data were collected on birth history, diagnosis of CHD, underlying chromosomal or genetic abnormalities, medication history, surgery, ventilator care, and exposure to iodine contrast media (ICM). Results of neonatal screening tests (NSTs) and TFTs were reviewed. Results A total of 36 patients (29 transient, 7 permanent) showed thyroid dysfunction. Among the seven patients with permanent hypothyroidism, three had an underlying syndrome, three showed abnormal NST results, and one was admitted to the intensive care unit for macroglossia and feeding cyanosis. We found that infants with transient thyroid dysfunction had a lower birth weight and were more commonly exposed to thyroid disrupting medication and/or ICM. However, these risk factors were not significant. A total of 8 patients with a history of ICM exposure showed thyroid dysfunction. Excluding 3 patients with elevated thyroid stimulating hormone before ICM exposure, 5 patients recovered from transient thyroid dysfunction. Conclusions We observed thyroid dysfunction in two-thirds of CHD infants (53.7% transient, 13.0% permanent) who had risk factors and received TFT screening within 100 days, despite normal NSTs. Further studies with larger sample sizes are required to revise the criteria for TFT screening in CHD infants.